Analisis just in time sebagai alat bantu perencanaan persediaan untuk memaksimalkan laba - Segawati, Zen Nufus (El Dinar: Jurnal Keuangan dan Perbankan Syariah, 2016)
The purpose of this study was to determine the application of JIT as inventory of planning to maximize profit at the karya perdana. This study used decriptive qualitative approach. Analysis of the data used the production cost analysis. Then, the analysis of the implemetation of JIT used the MPR for scheduling the purchaseof raw materials, the analysis of performance with line balancing to make improvements and production efficiencies. After that, compared the cost of production beforeand after implementing of JIT. The results showed that a decline in production costs after the implementation of JIT methods. By using the method of JIT, companies just made the purchase of raw materials used only as needed per day. This causes raw material costs decreased by 8.51%. with JIT method was also carried out repairs of production of cycle time for production effeciency at the cost of direct labor costs but no change whereas the use of engine-related electricity costs in overhead costs were calculated based on the actual production of cycle time thus causing a decrease in cost of 2.53%, as result of a decrease in these costs, the company had increased earnings by 6.67% comapared with the methods applied by the company without it